Detection of Herpes simplex Virus type-1 and 2 (HSV-1 and HSV-2) IgG and IgM Antibodies with ELISA in Sera of Pregnant Women (Annals of Medical Research, 2021)
None
Keywords: Pregnants, Herpes simplex virus, ELISA, Antibody